2017
DOI: 10.21767/2254-6758.100087
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Laparoscopic Cholecystectomy to Open Cholecystectomy: An Analysis in a High Risk Group of Patients

Abstract: Background: Laparoscopic cholecystectomy (LC) has revolutionized minimally invasive surgery, considered as gold standard and increasing number of procedures are done for patients with various high risk comorbid conditions. LC today can be as straightforward operation, but may also be an operative approach fraught with underlying complexities necessitating conversion to open cholecystectomy leading to longer operative time, longer hospital stay and more postoperative morbidity and higher hospital costs. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…Since the introduction of laparoscopic cholecystectomy (LC), it rapidly gained popularity, almost replacing open cholecystectomy in many countries, [1][2][3][4][5] and several studies showed that LC can be successfully introduced in developing and low-income countries, with satisfactory results. [3,[6][7][8][9][10][15][16][17], However, in Afghanistan, despite the fact that LC was introduced more than a decade ago, most cholecystectomies are done through an open approach, due to limited equipment, support services and manpower required for LC. [16,21] Mean age was 45.8 ± 13.5 years, where most of the patients were in 31-50-and 51-70-year age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the introduction of laparoscopic cholecystectomy (LC), it rapidly gained popularity, almost replacing open cholecystectomy in many countries, [1][2][3][4][5] and several studies showed that LC can be successfully introduced in developing and low-income countries, with satisfactory results. [3,[6][7][8][9][10][15][16][17], However, in Afghanistan, despite the fact that LC was introduced more than a decade ago, most cholecystectomies are done through an open approach, due to limited equipment, support services and manpower required for LC. [16,21] Mean age was 45.8 ± 13.5 years, where most of the patients were in 31-50-and 51-70-year age groups.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Conversion rate to open cholecystectomy is variable and has been reported from 1.9-14.7%. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It is noteworthy that the data regarding safety of day care LC came from developed countries with wellestablished norms for day care surgery, and should not be extrapolated to surgical practice everywhere. [8] However, several studies show that LC can be successfully introduced in developing and low-income countries, with satisfactory results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from a single university medical center recorded a 2.6 percent conversion rate, and among converted cases, the diagnosis of acute cholecystitis was more frequent. 2 (3.3 %) laparoscopic procedures involved conversion to open surgery due to blurred vision due to difficult dissection and bleeding in the current study [20][21][22] 23 . Many prospective randomized trials have shown that early laparoscopic cholecystectomy avoids possible risk of late complications such as gangrenous or emphysematous cholecystitis & is the preferred technique for treating the acutely inflamed gallbladder within 7 days of the onset of symptoms without a rise in postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion to open surgery from laparoscopic cholecystectomy was encountered because of recurrent management of multiple episodes of acute cholecystitis and avoiding definitive surgery because of associated comorbidities. The conversion decision is considered as a sound judgment to avoid complications and reduce morbidity (Hussain et al 2017).…”
Section: Discussionmentioning
confidence: 99%